The impact of covid-19 on poverty alleviation: Empirical evidence from Somalia - Razak, Dzuljastri Bin Abdul; Nor, Bile Abdishalan (Jurnal Ekonomi & Studi Pembangunan, 2024)
This study provides valuable insights into the impact of COVID-19 on poverty alleviation in Somalia, focusing on three factors namely, government Intervention, financial literacy and digital financial inclusion are linked to poverty alleviation. This study utilized a quantitative research approach employing a descriptive research design. The data collection aspect was carried out by the researchers through face to face and an online self-administered questionnaire which can be filled out by respondents from various backgrounds. A survey was conducted with 277 micro-entrepreneurs using both on line and face to face methods. The data obtained is process using SPSS. The findings indicated positive and significant relationship with all three factors namely government intervention, financial literacy and digital financial inclusion in Somalia. The findings of this study suggest that the government of Somalia should focus on these three areas to help to alleviate poverty. By providing social safety nets, increasing financial literacy, and promoting digital financial inclusion, the government can help to improve the lives of millions of people in Somalia. To achieve long-term poverty reduction and development, it is crucial for Somalia to move away from dependency on external assistance and prioritize self-sufficiency. One limitation of this study is its relatively small sample size of 277 micro-entrepreneurs. In a larger sample size, there could be more diverse perspectives and experiences that could potentially yield different results. Therefore, further research with a larger sample size is needed to obtain a more comprehensive understanding of the impact of COVID-19 on poverty alleviation in Somalia.